Clearing Up Correlationism: Goldschmidt, Meillassoux, and the Problem of Finitude. - Meyerson, Ben (Philosophy Today, 2023)
In After Finitude, Quentin Meillassoux speculates from the principle of noncontradiction's a priori enclosure toward a standpoint of absolute contingency. Based on his propositions, I argue that his thinking continues to reproduce a contradiction between the finitude of the subject and the infinitude of the noumenal world. Accordingly, I eschew the principle of noncontradiction in favor of a principle of contradiction derived from Hermann Levin Goldschmidt's Contradiction Set Free. Goldschmidt formulates contradiction as an Either-And-Or whereby the two contradictory terms share a space between them in which there elapses a continuous process of negotiation. If the relation between finitude and infinitude is an Either-And-Or, then there is an interpenetration between the finite and the infinite, between bounded subject and noumenal world. Goldschmidt's method reinvigorates the contradiction with which Meillassoux is grappling and introduces a more immanent mode of infinitude that echoes certain Spinozist and pre-Spinozist strains of Jewish thought.